Successful Percutaneous Coil Embolization of a Ruptured Internal Iliac Artery Aneurysm Remnant after Abdominal Aortic Aneurysm Repair via the Deep Iliac Circumflex Artery - Ohmine, Takahiro (The Editorial Committee of Annals of Vascular Diseases, 2014)
Here, we describe a case of an 83-year-old man treated with percutaneous IIA coil embolization for an enlarging remnant IIA aneurysm. CT scans revealed a contained rupture and persistent flow in the right IIA with the enlargement. We selected percutaneous embolization via the deep iliac circumflex artery, that was communicating with the superior gluteal artery and the IIA. Coil embolization of the arteries supplying the IIA aneurysm was successfully performed with 12 embolization coils placed in the IIA and its branches. The absence of blood flow and shrinkage of the aneurysm were confirmed by CT three months after embolization.